Home Range of the Endangered Beale's Eyed Turtle (Sacalia bealei) and the Implications for Conservation - Xiangyu Yuan; Qingru Hu; Rongping Bu; Jiangbo Yang; Liu Lin; Hai‐Tao Shi (Ecology and Evolution)
ABSTRACT The Beale's Eyed Turtle (Sacalia bealei) is endemic to China and endangered primarily due to poaching and habitat loss. However, limited ecological information for this species hinders conservation actions. Using radiotelemetry, we determined the home range size of S. bealei in its natural habitat, collecting 769 valid activity locations from nine turtles (3 males, 6 females). The line home range size (LHR), home range area (HR, 95% minimum convex polygons), and core home range area (CHR, 50% fixed kernel density estimation) were about 185 m, 0.626 ha, and 0.089 ha, respectively. Bayesian and Cliff's delta analyses revealed no significant sex‐based differences in LHR, HR, or CHR overall or during the non‐breeding season. However, during the breeding season, females exhibited significantly larger HR and CHR than males (Cliff's delta = 1, 95% CI [0.14, 1]; Bayes factors 2.06–3.27), reflecting increased movement for breeding. Home range overlap ranged from 0.30 to 0.33 across pair types annually, with no significant differences between the breeding and non‐breeding periods (Mann–Whitney U tests, p > 0.05). By highlighting species' vulnerability to habitat fragmentation and anthropogenic pressure, our findings emphasize the urgent need for strategic conservation interventions.